2001
DOI: 10.1080/02701367.2001.10608972
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Commitment among Participants in an Extended Day Physical Activity Program

Abstract: This study examined underserved youth participants' perceptions of commitment to an extended day physical activity program using Hellison's (1995) responsibility model. Seven participants ranging in age from 12 to 15 years participated in the study. Two personal interviews and a focus group interview were used to obtain participants' perceptions ofprogram commitment. Results revealed that program organization, personal characteristics, development of interpersonal relationships, and the program environment inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
32

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 20 publications
5
19
0
32
Order By: Relevance
“…Similarly, both models include elements that can promote relations among students such as cooperative learning, affiliation or group meetings, which could have reinforced significantly the relations among students. Previous studies have showed that the relationship among students that had experienced SE (García et al, 2012;Perlman & Goc, 2010) or TPSR (Schilling, 2001;Ward, Parker, Henschel-Pellett, & Pérez, 2012) had improved.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, both models include elements that can promote relations among students such as cooperative learning, affiliation or group meetings, which could have reinforced significantly the relations among students. Previous studies have showed that the relationship among students that had experienced SE (García et al, 2012;Perlman & Goc, 2010) or TPSR (Schilling, 2001;Ward, Parker, Henschel-Pellett, & Pérez, 2012) had improved.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, other researches have reached better improvements having implemented the PSRM for more time, what allowed teachers to spend more time to develope each level of personal and social responsibility [33,34]. Therefore, some of the future works proposed suggest the reduction of the number of participant centres at the same time that the increase of the intervention duration (a whole academic year).…”
Section: Discussionmentioning
confidence: 99%
“…As a close relationship with the coach or mentor strongly influences the commitment of youths to a program (Schilling, 2001), befriending may be a prerequisite for other mentoring activities. However, the efforts of mentors should not be limited to relationship building; they should also recognize the developmental needs of youth and focus on developing competence and character (Hamilton & Hamilton, 1992).…”
Section: Jpes ®mentioning
confidence: 99%